Colorectal Cancer Screening Programme: Algarve Preliminary data. (13th November 2019) - Correia, M; Cancela, M; Caldeira, P; Morera, J; Cardoso, C; Pereira, R; Ferrinho, D; Vale, L
Abstract: Problem: The burden of disease for oncological problems is significant in Portugal. Population-based screenings, such as colorectal cancer screening (CCS) with faecal occult blood tests (FIT) is a priority program to reduce the burden of disease and a cost-effectiveness measure. Description problem: Algarve CCS started in 2017, to early detect colorectal cancer reducing morbidity and mortality. Screening strategy to detect and remove cancer precursors (adenomas) and early cancer detection with less invasive treatment using a non-invasive stool test was selected. A quantitative faecal immunochemical test for haemoglobin (FIT) with higher sensitivity for adenoma and cancer, specific for human globin with no dietary restriction, with a single sample screening is considered a test with higher participation. Target population all gender from 50 to 75 are invited to participate in the CCS by letter. Screening interval is 2 years and FIT cut-off- 117 (ng Hb/mL). Software was used to manage all CCS. Health units distribute the test and a flyer. All FIT-positive were invited to do a full colonoscopy at University Hospital. Results: A preliminary descriptive analysis (2017/2019) was made. After exclusions 25017 of target population participate 34, 4%(n = 8594), 27.5%(n = 6883) submitted it for analysis, 3.9% (n = 266) had positive FIT and were invited for a full colonoscopy with 57.5% (n = 153)participation rate. Cancer detection was 0.9‰ and adenomas detection rate was 9.9%. FIT positive with colonoscopy 3.9% (n = 6) had carcinoma and 44.4% (n = 68) had adenoma. Lessons: Some operational changes were made to improve participants and professionals adherence to CCS. Pathology observed in the positive cases, reinforce the need to implement strategies to increase literacy, raise public awareness, keep the screening test and improve accessibility of health facilities. Key messages: The importance of a colorectal cancer early diagnosis prevent aggressive interventions in a precancerous phase. The importance of a colorectal cancer early diagnosis improves survival and population quality of life.